Compound heterozygosity for Hb S and Hb S-Oman : Case report - Suresh Venugopal; Alphonsa Shaju; Suchata Dhuri; Thuraiya Al-Harthy; Khalid B Jabal (Sultan Qaboos University Medical Journal, 2008)
The haematological and clinical findings of a three year old Omani girl, phenotypically compound heterozygote for Hb S and Hb S Oman, are presented, further substantiated by family studies. The necessity of reviewing cases with sickle cell haemoglobin in Oman is stressed.